New discourses in medieval canon law research
1 online resource.
Keywords: New Discourses in Medieval Canon Law Research offers a new narrative for medieval canon law history which avoids the pitfall of teleological explanations by taking seriously the multiplicity of legal development in the Middle Ages and the divergent interests of the actors involved. The contributors address the still dominant ‘master narrative’, mainly developed by Paul Fournier and enshrined in his magisterial Histoire de collections canoniques . They present new research on pre-Gratian canon collection, Gratian’s Decretum , decretal collections, but also hagiography, theology, and narrative sources challenging the standard account; a separate chapter is devoted to Fournier’s model and its genesis. New Discourses thus brings together specialized research and broader questions of who to write the history of church law in the Middle Ages. Contributors are Greta Austin, Katheleen G. Cushing, Stephan Dusil, Tatsushi Genka, John S. Ott, Christof Rolker, Danica Summerlin, Andreas Thier and John C. Wei.